Analisis Tingkat Penerimaan Pengguna Layanan Cloud Storage Menggunakan Metode Technology Acceptance Model 3 (TAM3) Pada Dinas Perpustakaan Dan Arsip Kota Pekanbaru - Adinda Zilly Arsyika; Ery Safrianti; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Data are valuable information in an agency or an institution, both engaged in politics, culture, education, economics and etc. Therefore, data very important to be properly maintained and stored by the relevant agencies. Nowadays, data are no longer just archived on a piece of paper but also stored in a storage medium that uses internet network to access it. Library and Archives Service (DISPUSIP) in Pekanbaru,Riau Province, Indonesia is a government institution that embodies the seriousness of the local Government in Pekanbaru to educate the life of Indonesia. DISPUSIP Pekanbaru, has problems in managing data storage. In this case, it is necessary to have file management which includes data storage and file sharing in a computer that is made a server, so all data will be stored centrally. Data storage on a server side or known as cloud computing is a technology where is owners data do data storage on server storage or known as cloud storage. Cloud storage used in this study is OwnCloud. After OwnCloud operates, it is required analyzing the use of OwnCloud. OwnCloud is a private cloud service. With OwnCloud, IT can maintain complete control over all documents or archives in DISPUSIP, knowing exactly where the data is at all times and deciding who might or might not have access to certain documents and folders. This analysis is intended to determine the acceptance of Cloud Storage with a OwnCloud that will be assessed by DISPUSIP employees. Analysis in this study will use the Technology Acceptance Model 3 (TAM3) method by revealing the influences of 16 hypotheses. Computer Anxiety has a positive impact on Perceived Ease Of Use, Computer Self Efficacy has a positive impact on Perceived Ease of Use, Image has a positive impact on Perceived Usefulness, Job Relevance has a positive impact on Perceived Usefulness, Object Usability has a positive impact on Perceived Ease of Use, Output Quality has a positive impact on Perceived Usefulness, Perceived Ease of Use has a positive impact on Behavioral intention, Perceived Ease of Use has a positive impact on Perceived Usefulness, Perceptions of External Control has a positive impact on Perceived Ease of Use, Result Demonstrability has a positive impact on Perceived Usefulness, Subjective Norm has a positive impact on Image, Subjective Norm has a positive impact on Perceived Usefulness, Behavioral Intention does not have a positive impact on Use behavior, Computer Playfulness does not have a positive impact on Perceived Ease of Use, Perceived Enjoyment does not have a positive impact on Perceived Ease of Use and Perceived Usefulness does not have a positive impact on Behavioral Intention. From the test results 12 hypotheses have a positive impact and 4 hypotheses do not have a positive impact on research in DISPUSIP. Keywords: Cloud Storage, Cloud Computing, OwnCloud , Technology Acceptance Model 3 (TAM3), Library and Archives Service (DISPUSIP) Pekanbaru.